North Ghazvin fault system: active faulting in Southern edge of the Central Alborz - Hamid, Nazari (ՀՀ ԳԱԱ հրատ.)
In this paper we used morphotectonic study for more clarifying recent geometry and kinematic of the North Ghazvin fault as the closest active fault to Ghazvin city. The North Ghazvin is a compressional left-lateral fault between the Cenozoic rocks and the Plio-Quaternary alluvial deposits.These alluvial deposits,geometrically, could be subdivided into two main western- and eastern parts characterized by the north-dipping reverse faulting with a left-lateral strike-slip. Several large historical earthquakes have occurred along this inherited structure representing a high seismic potential, although it is not proved by a strong instrumental event yet. В данной статье мы применили морфотектоническое исследование с целью уточнения современной геометрии и кинематики Северо-Газвинского разлома, поскольку он является наиболее близко расположенным к городу Газвин активным разломом. Северо-Газвинский разлом представляет собой компрессионный левосторонний разлом между кайнозойскими породами и плиочет вертичными аллювиальными отложениями, который по геометрии можно подразделить на две главные части – западную и восточную, характеризующиеся образованием взбросов с падением на север и левосдвиговой компонентой. Несколько сильных исторических землетрясений имели место вдоль этой структуры, имеющей высокий сейсмический потенциал, хотя это и не было пока подтверждено сильным нструментальным событием.Այս հոդվածում օգտագործվել են մորֆոտեկտո- նական հետազոտությունները՝ առավել մանրամասն պարզաբանելու համար Ղազվին քաղաքին ամենամոտ գտնվող հյուսիսային Ղազվինի սալի երկրաչափությունն ու կինեմատիկան: Հյուսիսային Ղազվինը սեղմված ձախակողմյան բեկվածք է ցենոզոիկ ապարների և պլիո չորրորդական հասակի ալյուվիալ գոյացումների միջև, որը երկրաչափորեն կարող է ենթաբաժանվել երկու հիմնական՝ արևմտյան և արևելյան մասերի, որոնք բնորոշվում են հյուսիսային հակադարձ բեկմամբ ձախակողմյան շեղումով: Մի քանի մեծ պատմական երկրաշարժեր են տեղի ունեցել այս կառույցի երկայնքով, որոնք ներկայացնում են բարձր սեյսմիկ պոտենցիալ, չնայած սա դեռևս չի հաստատվել որևէ ուժեղ կարևոր դեպքով:
Keywords: Science; Geology; Tectonics